Facilitation of Vaginal Delivery in an Infant with Complete Heart Block Secondary to Maternal Anti-Ro Antibodies. (21st November 2017) - Thornton, E.; Tripathi, L.; Shebani, S.; Bruce, I.; Byrd, L.
Abstract : Congenital heart block (CHB) is a rare disorder that may be associated with a high morbidity and even mortality, with a risk of death both in utero and during infancy. Women with serum titres of anti-Ro and/or anti-La antibodies carry a risk of CHB of 1–5% in their offspring, with a recurrence risk of approximately 20%. We present a case of a 36-year-old female with a pregnancy complicated by congenital heart block. Autoimmune profiling at booking showed she was positive for lupus anticoagulant and anti-Ro antibodies. A fetal echocardiogram at 21 + 3 showed complete heart block. She was monitored throughout the remainder of her pregnancy with serial growth scans, cardiovascular profiling, and BPP scoring. She had a normal vaginal delivery at term to a female infant.